BRIDGING THE GAP OF WRITING FOR HEALING AND ISLAMIC SPIRITUALITY - Kurniawan, Redite; Aziz, Husein (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aimed to bridge the gap between writing for healing and Islamic spirituality by exploring the experiences of four Muslim students in MTs Terpadu Ar-Roihan, Lawang Malang. The study utilized a case study approach to analyse the expressive writing content of the participants, focusing on the integration of Quranic values and teachings. The participants, aged 13 to 15, were selected based on their emotional difficulties and behavioural problems with five-session treatment plan for participants in the writing intervention (the principles and guidance found in the Quranic scriptures). The findings revealed that the participants demonstrated a deep connection to Allah and a strong awareness of the creation and destiny of life. Their writings reflected their hopes, prayers, and apologies, seeking guidance and forgiveness to others. The expressive writing also exposed their emotional expressions, with some participants expressing sadness, self-blame, frustration, and anger. The study concludes that there is a meaningful connection between writing for healing and Islamic spirituality